Avaliação do ciclo da vida do programa de coleta seletiva do Município de João pessoa- PB, Brasil - Martins, Wanessa Alves (2017)
Solid waste from residences have significant potential to generate environmental impacts. Depending on how the steps of the management are carried out (packaging, transport, process, treatment and final disposal), the waste can cause impacts through gaseous, liquid and solid emissions in various stages of the system. When hiring the life cycle assessment - LCA to analyze solid waste management, it is possible to identify the environmental impacts related to its management, as well as choose better models that respond to local expectations, in a way that produce a result that optimize the power generation and minimize the impacts. The main objective of this research was to analyze the life cycle of the collection selective program of solid waste in the municipality of João Pessoa, Paraíba State, Brazil. Researches were carried out with the Special Municipal Authority of Urban Cleaning - SMAUC and interviews were conducted with the Presidents of the recyclable materials associations in each core of selective collection of the municipality for the diagnosis of commercial structure. The life cycle analysis was performed following the recommendations of ISO 14.040 (2014). The functional unit adopted was a ton of solid waste generated. The software used was the SimaPro 8.0 and the method to analyze the impact was the CML, selecting the categories of: eutrophication, acidification, photochemical oxidation, global warming, ozone layer depletion, human toxicity, terrestrial ecotoxicity, aquatic ecotoxicity in fresh water, aquatic ecotoxicity in marine water, abiotic depletion (fossil fuels and minerals). In this way, as for the diagnosis in the nuclei of selective collection, it is concluded that the EMLUR supports all cores of selective collection (except the Catajampa core), ceding or leasing warehouses, providing lunch, uniforms, personal protective equipment (PPE), equipment maintenance, among other actions. The warehouses of the nuclei have suitable area for segregation and weighing of the recyclable materials, except the Cabo Branco core that has a reduced space and absence of coverage in locations where the materials are stored. The division of profits, in most of the nuclei, from the sale of recyclable materials is individual, and in equal parts only in Acordo Verde and Roger cores. It can be notice that the recycling process presented a subtle growth during the years of 2005 - 2015, compensating some categories of environmental impact. However, for the categories of photochemical oxidation, global warming, ozone layer depletion, human toxicity, aquatic ecotoxicity in marine water and eutrophication, the emissions of pollutants were above negative contributions generated by the step of recycling. It was found that the collection selective program of solid waste in the municipality needs to optimize some steps of its management. This optimization can be accomplished by increasing the quantity of solid waste sent to recycling, reduction of pollutants emitted from the burning of fossil fuels and reusing the gases produced in the landfill.